Whole Body Vibration Improves Spatial Memory, Anxiety-Like Behavior, and Motor Performance in Aged Male and Female Rats - Oroszi, Tamás; Geerts, Eva; de Boer, Sietse F.; Schoemaker, Regien G.; van der Zee, Eddy A.; Nyakas, Csaba (Frontiers in Aging Neuroscience, 2022)
Aging is a progressive process leading to functional decline in many domains. Recent studies have shown that physical exercise (PE) has a positive influence on the progression of age-related functional decline. Whole body vibration (WBV) is a form of passive stimulation by mechanical vibration platforms which offers an alternative for PE interventions, especially for aged individuals. WBV has been demonstrated to mimic the beneficial effects of PE on the musculoskeletal system, as well on the central nervous system. However, preclinical data with aged rodents are very limited. Hence, the purpose of this experiment was to investigate the effects of a five weeks WBV intervention with an aged animal model on memory functions, anxiety-related behavior and motor performance. Eighteen months old male (N=14) and female (N=14) Wistar rats were divided into two groups: vibration and pseudo-vibration. Animals underwent a 5 weeks WBV intervention with low intensity (frequency of 30 Hz and amplitude of 50-200 micrometer) stimulation. After five weeks, cognitive and motor tests were administered including open-field, novel and spatial object recognition, grip-hanging and balance-beam tests. Vibration-treated rats showed a decrease in their anxiety level in the open field test compared to the pseudo-treated controls. In addition, vibration-treated male animals showed significantly increased rearing in the open-field test compared to their pseudo controls. Spatial memory was significantly improved by vibration treatment, whereas vibration had no effect on object memory. Regarding motor performance, both grip strength and motor coordination were improved by vibration treatment. Our results indicate that WBV seems to have comparable beneficial effects on age-related emotional, cognitive and motor decline as what has been reported for active physical exercise.